Implementasi Metode Al-Miftah Lil Ulum Dalam Meningkatkan Standar Mutu Kemampuan Membaca Kitab Kuning Santri Di PP Roudlotut Thohirin Sengon Pringgodani Bantur Malang - Nizar, Muhammad Jamalun; Abror, Turmudzi; Samsuri, Hamam (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Islamic boarding schools (Pondok Pesantren) in Indonesia emphasize the teachings of early scholars found in kitab kuning, which are based on the principles of Ahlu Sunnah Wal Jamaah. These texts cover subjects such as fiqh (Islamic jurisprudence), aqidah (creed), tasawwuf (Sufism), and linguistic sciences like nahwu (grammar), sharaf (morphology), language, and balaghah (rhetoric). Books like Jurmiyah, Imrithi, and Alfiyah are commonly used for learning nahwu and sharaf. As an innovation, Pondok Pesantren Sidogiri, through Batartama, developed the instructional book Al-Miftah Lil Ulum to help students better understand and read the kitab kuning. Based on this background, the researcher proposes the following research questions: 1) How does the study group method using Al-Miftah Lil Ulum improve the quality standards of students' ability to read the kitab kuning from the perspective of behaviorist learning theory at PP Roudlotut Thohirin? 2). How does the Al-Miftah Lil Ulum method serve as a stimulus? 3). What is the form of evaluation for the Al-Miftah Lil Ulum method? This research is qualitative, using a case study design. Data collection methods include participant observation, in-depth interviews, and documentation. Data analysis employs a flow model technique, consisting of data reduction, data display, and conclusion drawing. The findings indicate improvements in students' learning outcomes, including better mastery of material, enhanced ability to read kitab kuning, and adherence to proper reading rules. However, challenges in implementing the Al-Miftah Lil Ulum method include inadequate facilities and infrastructure as well as a shortage of qualified teaching staff.